Conceptualizing the notions of human-being and human-person in terminal discharge - Jackson Coy (Bangladesh Journal of Bioethics)
Terminal discharge or discharging terminally ill patients from hospitals in Tanzania as any other end-of-life care decision does not go without moral dilemma. Although the resolutions of end-of-life care decisions in hospitals in Tanzania focus much on material order rather than moral order, this paper shows the moral imperative of terminal discharge. The paper picks one of the controversial bioethical moral issues that are always raised in end-of-life decisions; ‘the distinction between human beings and human-person’ and analyzes it through linguistic categories of Kiswahili language. From the reflections on the semantic charge of human beings (binadamu in Kiswahili) and human-person (mtu in Kiswahili), it is possible to infer that their distinction holds to moral criterion that may influence terminal discharge in Tanzania. The former is a quality that is inborn in so far as anyone who is born as a human being has nature humanity (ubinadamu). The latter, however, introduces a nuance according to which the moral component enables to take humanity away from animality up to humanness (utu). The question is that of knowing, in terminally ill discharge, whether the end-of-life decision makers act out of humanity (ubinadamu) or humaneness (utu).